Derivational Morphology and Compounding: a descriptive study towards enhancing the learning and teaching of Gugbe - Anthony Horeb Midjochedo (Journal of Science and Knowledge Horizons, 2025)
This study examines the morphological processes involved in word formation in Gugbe, a language spoken in West Africa, with particular focus on Nigeria and Benin. Unlike previous research, which has primarily explored Gugbe syntax (Aboh, 2017; 2007; 2005; 1999; 1998), this study shifts focus to morphology, addressing the gap in understanding of word-formation processes in the language. Building on Adjibi’s (2020) work on Gugbe names and words associated with ‘ogú’ (the god of iron), the objectives here are to outline key Gugbe word-formation mechanisms and compare them to English morphological structures. Methodologically, the study analyzes words, phrases, and sentences from everyday speech and native songs, assessing morphological markers. Results show that Gugbe employs diverse processes: prefixation (e.g., otò, ‘country’), suffixation (mítọn, ‘our’), compounding (Gbé-kanlin, ‘wild animal’), reduplication (dagbedagbe, ‘very good’), calquing (Sȩnami, ‘God gave it to me’), clipping under calquing (Mìjoședo), and borrowing (blȩdi, ‘bread’). Notably, while most compound words in Gugbe are right-headed (e.g., gbékanlin, ‘wild animal’), some are left-headed or non-headed. This investigation expands understanding of Gugbe morphology, enriching linguistic resources for Gugbe learners and prompting further research into Gugbe lexical innovation.